Eating is a political act: food activisms and the construction of Banquetaço in Belo Horizonte (Simbiótica. Revista Eletrônica, 2025)
The paper seeks to describe and analyze the repertoires of action mobilized at the Banquetaço promoted in Belo Horizonte to defend the National Council for Food and Nutritional Security (CONSEA) in 2019. Based on documentary analysis and semi-structured interviews, we identify innovative aspects in the mobilization of repertoires performed by this “act-commensality”, namely: institutionalized participation, bureaucratic activism, proximity politics, direct action and food consumption. We conclude that Banquetaço represented a temporary coalition of two generations of food activism — the first related to the politicization of food in the institutional sphere and the second to the politicization of food and eating through new political, ethical and aesthetic strategies. This coalition, in turn, revealed mutual learning and divergences. The research suggests that the category of generations of activism can help in theoretical refinement to understand the change in interaction repertoires and politicization of food in Brazil.
Keywords: Food Activism; Repertoires of Interaction; Food and Nutrition Security; Banquetaço